2021
DOI: 10.1101/2021.04.02.21254493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Humoral response to Pfizer mRNA vaccine against SARS CoV2, in patients with autoimmune inflammatory rheumatic diseases and the impact on the rheumatic disease activity

Abstract: Background: The registration trials of mRNA vaccines against SARS CoV2 did not address patients with autoimmune inflammatory rheumatoid diseases (AIRD). Aims: To assess the humoral response to mRNA vaccine against SARS CoV2, in AIRD patients treated with immunomodulating drugs and the impact on AIRD activity. Methods: Consecutive patients treated at the rheumatology institute who received their first SARS-CoV-2 (Pfizer) vaccine were recruited to the study, at their routine visit. The patients were invited for… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 4 publications
(4 reference statements)
3
11
0
Order By: Relevance
“…Our results are in line with the recent literature [ 19 24 ]. Reduced antibody titers and negative effect of DMARDs among patients with IMD were reported in the majority of the studies investigating mRNA vaccine response.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results are in line with the recent literature [ 19 24 ]. Reduced antibody titers and negative effect of DMARDs among patients with IMD were reported in the majority of the studies investigating mRNA vaccine response.…”
Section: Discussionsupporting
confidence: 94%
“…Antibody response to vaccine against SARS-CoV-2 in patients with IMD or patients on immunosuppression has been investigated in a few studies recently [ 19 24 ] and notably in all, mRNA vaccine was studied. To our knowledge, ours is the first with chemically inactivated vaccine (CoronaVac).…”
Section: Discussionmentioning
confidence: 99%
“…Our report adds to the results of a series of studies that have investigated humoral and cellular responses to SARS-CoV-2 vaccination in patients with a history of B-cell depleting anti-CD20 therapies. 11 , 12 , 16 , 28 , 29 , 30 , 31 Deepak and colleagues 11 first reported a 36-fold decrease in vaccine-induced anti-spike IgG titres in patients with B-cell depleting therapies. Simon and colleagues 30 and Apostolidis and colleagues 29 reported no detectable or severely diminished vaccine-induced humoral immune responses compared with controls in two smaller series of patients with severely depleted B-cell counts, but both studies reported detectable cell-mediated immunity in these patients.…”
Section: Discussionmentioning
confidence: 99%
“… 10 There is an urgent need for evidence-based recommendations for administration of SARS-CoV-2 vaccines in immunocompromised patients, since in the absence of randomised controlled trials, current recommendations to delay B-cell-depleting therapies are based on previous influenza vaccination studies 7 and emerging humoral data on immune responses to SARS-CoV-2 vaccines in immunocompromised patients. 11 , 12 , 13 , 14 , 15 , 16 An improved understanding of humoral and cell-mediated responses following vaccination against SARS-CoV-2 in patients treated with anti-CD20-depleting agents is a prerequisite for the development of individualised vaccination strategies for this population. Notably, longitudinal observational data after SARS-CoV-2 infection and after mRNA vaccine administration has provided evidence that, in COVID-19 and after vaccination, cell-mediated immune responses were crucial for humoral immunity 17 , 18 , 19 , 20 , 21 and might provide protection even in patients with B-cell depletion.…”
Section: Introductionmentioning
confidence: 99%
“…Our report adds novelty to the results of a series of smaller studies that have previously investigated humoral and cellular responses to SARS-CoV2 vaccination of patients with a history of B-cell depleting anti-CD20 therapies 11,12,16,29,30 .…”
Section: Discussionmentioning
confidence: 79%